¨Propuesta de Metodología par la Evaluación de la Sustentabilidad en Obras de Construcción para el Turismo en la Cayería Noreste de Villa Clara - Acosta Monzón, Lázaro Abel (Universidad Central "Marta Abreu" de las Villas, 2008)
The work shows a proposal of a method for the Evaluation Qualitative of the Sustainability in the Works of Built for the Tourism of the Northeast Keys of Villa Clara. For their making firstly was carried out a summary of data on the topic of the Sustainability, the Tourism and the Sustainable Tourism to international level, for Latin America and the Caribbean as well as the case from Cuba and specially the Northeast Keys of Villa Clara. Important works carried out by other authors were considered that they approach the thematic of the Sustainability and the Methodologies of Evaluation. In this works the procedures are constituted in their majority for three fundamental elements: Work with Committee of Experts, the Indicators-Attributes System and the Process of Evaluation properly said. It also come this way the proposal of an evaluative instrument of the Sustainability in tourist constructions not existent in of the Northeast Keys of Villa Clara, which with a enriching and posterior improvement could come to be of use not only local but also national, being used as help for the taking of decisions in the conception of a project and in turn in order to correct deficiencies in the built. Finally they are arrived to general conclusions and they are offered the pertinent recommendations; leaning everything for a group of important annexes in order to deepen in the topic in question and the bibliography used for the making of the same.
Keywords: Evaluación Cualitativa de Sustentabilidad; Obras de Construcción; Turismo en la Cayería Noreste; Villa Clara; Tourism